MERETAS KETERASINGAN GURU SEJARAH SMA SUMENEP (Jurnal Pendidikan Sosiologi dan Humaniora, 2021)
Education has experienced its noble value. Education policy is always intertwined with power. Actualized from government policies that distort PKI material in schools. This makes the teacher experience alienation. The condition of alienation also occurs in the history teacher of SMA Sumenep. However, previous studies have not examined history teachers critically. Therefore, this study examines the isolation of the history teacher at SMA Sumenep from a critical education perspective. This research is qualitative with data collection of observations, interviews, and documentation. The results of the study show that there are differences in interests between history teachers and the government. In addition, education leads to black pedagogy, because the learning process is scary.